Suspicious Prenasal Skin Thickness-to-Nasal Bone Length Ratio: Prevalence and Correlation with Other Markers in Second and Third Trimester Fetuses with Down Syndrome - Hagen, A.; Albig, M.; Keller, T.; Stumm, M.; Entezami, M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: To assess the prevalence and value of a suspicious prenasal skin thickness-to-nasal bone length ratio (PT/NB ratio) in comparison to other established markers in a large population of Down syndrome (DS) fetuses.Materials and Methods: This was a retrospective study of 139 DS fetuses and 530 normal fetuses scanned after 14 + 0 weeks of gestation. To characterize diagnostic performance, we used the ROC curve approach. The presence or absence of a PT/NB ratio > 0.8 and 11 other markers were assessed in the group of DS fetuses. A correlation analysis was performed in order to investigate associations between PT/NB ratio and other markers.Results: Among DS fetuses the median PT/NB ratio was 1.06 (IQR 0.729) and was significantly higher compared to normal fetuses with 0.62 (IQR 0.148), (p < 0.001). Gestational age had no influence on the PT/NB ratio. A PT/NB ratio > 0.8 had the highest prevalence of all markers with 89.2 % in the group of DS fetuses, 3 cases were negative for all markers and 3 cases were positive only for PT/NB ratio > 0.8. Marker-specific comparison between prevalences of a suspicious PT/NB ratio with respect to the presence or absence of other markers was statistically significant for hypoplastic NB and major anomalies (p < 0.05). Utilization of at least one of the following five markers was sufficient for detecting 136 out of 139 fetuses with trisomy 21: suspicious PT/NB ratio, hypoplastic NB, nuchal fold thickness, white spot, shortened femur.Conclusion: The PT/NB ratio is one of the most powerful indicators of DS in the second trimester. It is objective to interpret, easy to measure, and is reproducible.
Keywords: prenasal skin thickness; nasal bone length; trisomy 21